DYNAMIC PARAMETERS OF ENDOTHELIAL DYSFUNCTION AFTER DIRECT METHODS OF REVASCULARIZATION IN THE PATIENTS WITH CHRONIC LOWER LIMB ISCHEMIA - Horlenko, F. V. (Проблеми клінічної педіатрії, 2018)
Abstract. Introduction. In surgical practice, angiogenesis is very important for predicting the results of surgical intervention on vessels. In the human body, endothelial cells form new capillaries in those localizations where they are in need. Such a phenomenon is observed in healing of wounds in the area adjacent to the damaged tissue, there is a short-term «outbreak» of capillary formation. Local irritation and local infection also cause proliferation of new capillaries, and when inflammation passes, many of the newly formed capillaries undergo reverse development and gradually disappear. Purpose. To investigate the dynamics of endothelial dysfunction after direct methods of revascularization in chronic lower limb ischemia. Material and methods. Endothelial damage was evaluated in the presence of desquamated endothelial cells (DEC) in the blood plasma of patients with an indicator that exceeds 2.77 × 105 v1 litreplasma. The method has high sensitivity and allows diagnosis of latent endothelial dysfunction Results. The results of the complex examination of the treatment of 30 patients, which are operated in the department of vascular surgery of the Zakarpattia Regional Clinical Hospital named after A.V. Andriy Novak from 2012 to 2018 on chronic ischemia in the case of obliterating atherosclerosis of the vessels of the lower extremities. All patients performed femoral and hypodermic bypass grafting. On the basis of the obtained results there is a decrease in the number of desquamated endothelial cells, indicating a significant reduction of endothelial dysfunction. Conclusions. Reducing the number of desquamated endothelial cells (from 6.12±0.21 x 105 to 3.9±0.08 x 105 in 1 liter of plasma) after direct methods of revascularization in chronic lower limb ischemia suggests a significant decrease in the level of endothelial dysfunction. The predominance of regeneration processes over the detection of apoptotic endothelial cells in intima of vessels and the number of desquamated epithelial cells indicates a rational choice of surgical intervention. The obtained results confirm the decrease in the degree of vascular damage, positive dynamic angiogenesis and the effectiveness of the therapy.